Earnings and education in Portugal, 1985-1991. Issue 7 (8th July 2014) - Sousa Andrade, João; Duarte, Adelaide; C.N. Simões, Marta
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the distributions of earnings and education in Portugal in the early years of European integration, 1985 and 1991, a period when Portugal experienced strong nominal convergence following EU accession. Design/methodology/approach – The paper explores the information provided by relative distribution analysis and covariate (education) decomposition to study the dynamics of the earnings distribution since these methodologies allow for the identification of polarization patterns that might have occurred over the period. More standard methodological instruments are also used as a reference: cardinal measures of inequality and the Lorenz stochastic dominance approach. Findings – The median and average earnings of employees increased and there was also a rise in earnings inequality. Relative to 1985, in 1991 there were more employees with very low earnings but also more 1991 employees with high earnings and there were also more employees at the bottom and top ends of the earnings distribution. The analysis of the relative earnings distribution by level of education reveals substantial differences for the top end of the distributions with the proportion of 1991 employees receiving the highest earnings higher than for the original 1985 cohort. A regional disaggregation confirms that the overall employees' earnings and education distributions characteristics are determined by the behaviour of coastal regions, while in the non-coastal regions a lower level of inequality is associated with lower levels of median and average earnings and a different polarization pattern. Originality/value – The paper shows that inequality is not a recent phenomenon in the Portuguese economy and thus might be one of the sources of the growth slowdown Portugal is experiencing since the turn of the century and might continue to hamper growth in the future deserving deeper investigation.